Earthquakes, moves, reconstructions: what we learned in Lima (XVII-XVIII) - Scaletti-Cárdenas, Adriana (2022)
The earthquakes of the seventeenth and eighteenth centuries were decisive for Lima, the City of the Kings. From the perspective of the history of architecture, the moments after the earthquakes are particularly interesting, especially the reconstructions of the great viceregal capital. What was rebuilt and why? What materials and methods were chosen and for what reasons? Where and how were the new lots laid out? Why was the city not moved, as it happened in other similar cases? This paper reflects on these questions and on what the presence of such disasters meant in the evolution of Lima and Peruvian immovable material culture.